Pengulu Uten’s Forest Management in Central Aceh: A Perspective of Fiqh al-Bi'ah - Gayo, Ahyar; Makinara, Ihdi Karim; Aristeus, Syprianus; Djuniarti, Evi; Putri Nungrahani, Ellen Lutya (AHKAM : Jurnal Ilmu Syariah, 2024)
Indonesia's legislation stipulates that forest management involves the active participation of indigenous communities, manifested in the form of pengulu uten in Central Aceh. However, it is essential to examine the degree to which the forest management model implemented by pengulu uten aligns with the principles of fiqh al-bī’ah in Islamic law. This study employs an empirical juridical approach with a qualitative methodology. The data was obtained through a literature review, focus group discussions, and interviews with reje kampung, pengulu uten, and other relevant stakeholders. The findings indicate that pengulu uten plays a significant role in forest management and supervision. They engage in community fostering, counseling, and socialization activities about protected forests, production forests, customary forests, and the utilization of forest resources. The existence of pengulu uten emerged long ago as customary institutions in forest management (in other Aceh regions called Pawang Glee), so in Aceh, their existence is strengthened in the Qanun of Central Aceh Regency No. 10/2002 concerning Gayo Customary Law. However, there may occasionally be inconsistencies in forest management process since the function of pengulu uten is not carried out synergistically with other forestry officials. In light of this, the forest management by pengulu uten is found to be in accordance with fiqh al-bī’ah principles. It includes the protection of nature as the essence of religion, the enhancement of faith through forest management, the responsibility of humans as Khalīfah to safeguard the environment, the practice of al-amr bi al-ma'rūf wa al-nahy ‘an al-munkar in forest management, and the maintenance of ecosystem equilibrium. Hence, this study emphasizes the significance of synergy among the government, pengulu uten, and the community in attaining sustainable forest management following the principles of fiqh al-bī’ah.  Abstrak: Peraturan perundang-undangan di Indonesia memandatkan pengelolaan hutan dengan melibatkan masyarakat Adat Aceh Tengah yang diwujudkan dalam bentuk pengulu uten. Maka, penting untuk mengkaji sejauh mana keserasian model pengelolaan hutan oleh pengulu uten dengan prinsip fiqh al-bī’ah. Penelitian ini menggunakan pendekatan hukum yuridis empiris dengan metode kualitatif. Data diperoleh melalui studi kepustakaan, FGD, dan wawancara dengan reje kampung, pengulu uten, dan stakeholders. Hasil penelitian menunjukkan bahwa pengulu uten memiliki peran signifikan dalam pengelolaan dan pengawasan hutan. Mereka melakukan kegiatan seperti membina, menyuluh, dan mensosialisasikan kepada masyarakat tentang hutan lindung, hutan produksi, hutan adat, dan pemanfaatan sumber daya hutan. Eksistensi pengulu uten muncul sejak dulu sebagai lembaga adat dalam pengurusan hutan (di wilayah Aceh lainnya disebut Pawang Glee) sehingga di Aceh, keberadaan mereka dikuatkan dalam Qanun Kabupaten Aceh Tengah Nomor 10 Tahun 2002 tentang Hukum Adat Gayo. Namun, dalam praktiknya saat ini fungsi pengulu uten tidak dilakukan secara sinergis dengan petugas kehutanan lainnya sehingga terkadang terjadi ketidakseimbangan dalam pengelolaan hutan. Padahal, pengelolaan hutan oleh pengulu uten sesuai dengan prinsip fiqh al-bī’ah yang dinilai baik karena mencakup perlindungan alam sebagai esensi agama, kesempurnaan iman melalui pengelolaan hutan, peran manusia sebagai khalifah yang melindungi alam, amar makruf nahi mungkar dalam pengelolaan hutan, serta menjaga keseimbangan ekosistem. Oleh karena itu, penelitian ini menekankan pentingnya sinergi antara pemerintah, pengulu uten, dan masyarakat dalam mencapai keberlanjutan pengelolaan hutan yang didasarkan pada prinsip fiqh al-bī’ah.